Evaluation of a newly developed piezo actuator-driven pulsed water jet system for liver resection in a surviving swine animal model. Issue 1 (January 2016) - Nakanishi, Chikashi; Nakano, Toru; Nakagawa, Atsuhiro; Sato, Chiaki; Yamada, Masato; Kawagishi, Naoki; Tominaga, Teiji; Ohuchi, Noriaki
Abstract Background Preservation of the hepatic vessels while dividing the parenchyma is key to achieving safe liver resection in a timely manner. In this study, we assessed the feasibility of a newly developed, piezo actuator-driven pulsed water jet (ADPJ) for liver resection in a surviving swine model. Methods Ten domestic pigs underwent liver resection. Parenchymal transection and vessel skeletonization were performed using the ADPJ (group A, n = 5) or an ultrasonic aspirator (group U, n = 5). The water jet was applied at a frequency of 400 Hz and a driving voltage of 80 V. Physiological saline was supplied at a flow rate of 7 ml/min. After 7 days, the animals were killed and their short-term complications were examined and compared between the two groups. Results No significant complications, such as massive bleeding, occurred in either group during the surgical procedures. The transection time per transection area was significantly shorter in group A than in group U (1.5 ± 0.3 vs. 2.3 ± 0.5 min/cm2, respectively, P = 0.03). Blood loss per transection area was not significantly different between groups A and U (9.3 ± 4.2 vs. 11.7 ± 2.3 ml/cm2, P = 0.6). All pigs in group A survived for 7 days. No postoperative bleeding or bile leakage was observed in any animal at necropsy. Conclusion The present results suggested that the ADPJ reduces transection time without increasing blood loss. ADPJ is a safe and feasible device for liver parenchymal transection.